On the covergence of an iteration method for solving the boundary value problem in tile theory of elasto - platic deformation processes - Bich, Dao Huy; Hop, Nguyen Cong (Vietnam Journal of Mechanics, 1985)
In this paper is proposed an iteration method, as the Iliousin' s method for solving the boundary value problem in the theory of elasto - plastic deformation processes. The convergence of this method, i. e. the existence and uniqueness of  solution of the boundary value problem are also considered.